Double-dose icotinib may induce the emergence of the EGFR exon 20 T790M mutation in non-small cell lung cancer patients harboring EGFR-sensitive mutation - Chen, Jianxin; Wu, Xilin; Wang, Junhui (Frontiers in Oncology, 2022)
Background: Acquired resistance to epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) inevitably occurs in non-small cell lung cancer (NSCLC) patients harboring EGFR sensitive mutations. There are approximately half of the patients who developed resistance to EGFR-TKIs treatment, of which mechanism remains undiscovered. We occasionally found that double dose icotinib as further line salvage treatment may induce the emerging mutation of EGFR exon 20 T790M in NSCLC patients. The present study, therefore, was conducted to explore the probability of emerging T790M mutation after exposure of double dose icotinib in metastatic NSCLC patients. Patients and Methods: Metastatic NSCLC patients who received double dose icotinib as salvage treatment after progressed on first generation TKIs and systematic chemotherapy were screened. Thereafter, patients who received a repeated next generation sequencing (NGS) test with tumor sample were further enrolled. The operation procedure of NGS was performed with the standard criterion. Finally, eligible patients with clinical characteristics, treatment procedures, as well as outcomes were reviewed and presented. Results: Three patients have been detected emerging T790M mutation after double dose icotinib exposure, with mutation frequency as 19.6%, 8.2%, and 87.5%, respectively. During the treatment of targetable TKIs including almonertinib or osimertinib, partial response was observed in two patients, and stable disease in the other. The progression-free survival by targetable TKIs for the patients was 3.7+ months (still in extension), 4.9+ months (still in extension), and 6.3 months. Manageable adverse events were observed during the treatment of TKIs. Conclusion: Results of the present study revealed that emerging EGFR exon 20 T790M mutation might be induced by double dose icotinib exposure in further line treatment. Patients with the emerging T790M mutation responded well to the treatment of targetable TKIs including almonertinib or osimertinib